1969
DOI: 10.1136/pgmj.45.530.761
|View full text |Cite
|
Sign up to set email alerts
|

Combined carbenicillin and gentamicin for prophylaxis of post-operative infection following major abdominal surgery

Abstract: SummaryBacteriological studies with carbenicillin and gentamicin individually and with the combination of these antibiotics suggest their effect to be additive in action and often synergistic. Of sixty-five organisms tested in vitro, the majority Gram-negative, forty-seven were resistant to ampicillin, thirtyseven to carbenicillin, twenty-four to gentamicin and only six to carbenicillin plus gentamicin.Out of sixty-seven patients undergoing major abdominal surgery, thirty were randomly allocated to receive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1977
1977

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although systemic antibiotics may be effective in reducing wound infection after appendicectomy (Bernard and Cole, 1964;Bloom, 1969;Polk and Lopez-Major, 1969), it would seem that only large doses of potent antibiotics, often in combination and given at or shortly before operation, have such an effect. Margery et al (1971), in a trial of systemic ampicillin or tetracycline, found no reduction in wound infections compared with the controls, although the duration of postoperative fever and the incidence of intraperitoneal complications were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although systemic antibiotics may be effective in reducing wound infection after appendicectomy (Bernard and Cole, 1964;Bloom, 1969;Polk and Lopez-Major, 1969), it would seem that only large doses of potent antibiotics, often in combination and given at or shortly before operation, have such an effect. Margery et al (1971), in a trial of systemic ampicillin or tetracycline, found no reduction in wound infections compared with the controls, although the duration of postoperative fever and the incidence of intraperitoneal complications were reduced.…”
Section: Discussionmentioning
confidence: 99%